Strategi Pembelajaran PAI Berbasis Karakteristik Peserta Didik di Era Digital - Ananda Dilonia; Refa Ayunda Melki; Gusmaneli (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study analyzes the strategies of Islamic Religious Education (PAI) learning based on student characteristics as a response to the increasingly complex challenges of the digital era. Using a literature study approach, this research integrates technology such as interactive applications, online multimedia, and collaborative platforms specifically designed to support student-centered learning. These strategies not only strengthen the understanding of moral and religious values but also enhance student engagement, foster independent learning, and help manage the impact of negative digital content. The findings emphasize the importance of collaboration between teachers, students, and technology to create PAI learning that is relevant, innovative, and aligned with the needs of the younger generation. This study also provides significant contributions to the development of an adaptive curriculum capable of addressing the challenges of learning in the digital era.